On‐Chip Chiral Mode Switching by Encircling an Exceptional Point in an Anti‐Parity‐Time Symmetric System. Issue 12 (30th September 2022) - Liu, Weiwei; Zhang, Yicong; Deng, Zhihua; Ye, Jianghua; Wang, Kai; Wang, Bing; Gao, Dingshan; Lu, Peixiang
Abstract: Dynamically encircling the exceptional point (EP) of an anti‐parity‐time (anti‐PT) symmetric system can achieve chiral mode switching between symmetry‐broken eigenmodes, which is especially important for developing nanophotonic devices. However, the realization of anti‐PT‐symmetric systems on a chip still remains significantly challenging as precisely controlling the parameters of nanophotonic structures is difficult. Herein, a novel anti‐PT‐symmetric system is designed and constructed on a silicon‐on‐insulator chip by taking advantage of subwavelength gratings to help engineer nanophotonic structures. Consequently, on‐chip chiral switching between symmetry‐broken eigenmodes is experimentally realized by dynamically encircling the EP in parametric space of the proposed anti‐PT‐symmetric system. Moreover, the achieved chiral mode switching exhibits high output power ratios (≥ 6.4 dB) at 1550 nm, wide‐band response that covers C‐band completely, and great thermal stability up to 90 °C, which indicate desirable performance features for practical applications in optical communication. This study paves an avenue for realizing on‐chip chiral switching between symmetry‐broken modes, which shows great promise for developing nanophotonic devices, such as optical switching, logic gates, and isolators, in optical telecommunication bands. Abstract : Dynamically encircling the exceptional point (EP) of an anti‐parity‐time symmetric system is demonstrated with coupled subwavelength‐gratings waveguides, which enables to realize a chiral switching of the symmetry‐broken eigenmodes on chip. The on‐chip chiral mode switching shows great promise for developing nanophotonic devices such as optical switching, logic gates, and isolators in the optical telecommunication bands.